Factors of Customers’ Channel Choice in an Omnichannel Environment: A Systematic Literature Review - Wolf, Lukas; Steul-Fischer, Martina (Proceedings of the European Marketing Academy, 51st (106350), 2022)
The proliferation of mobile devices and the continuous development of online technologies has led to an increasing variety of channels, leaving today’s customers with a choice of channel alongside the choice of product, service, or retailer. Any attempt to optimize customer experience and engage in successful omnichannel management will require a complete understanding of the processes around customers´ channel choice. This study conducted a systematic literature review to the end of identifying the factors involved in channel choice which appear in the scientific literature. The analysis of 111 relevant papers retrieved from bibliographic databases highlighted five principal categories of factors: the characteristics of a particular channel, customer needs, situation and context, customer characteristics, and characteristics of products or services. Alongside its presentation of an integrated conceptual framework, the review details a comprehensive agenda for future research.